Komunitas Pengabdi Seni Musik Tradisional Karinding di Kampung Jaha Tangerang - Tyas Siti Nur Asiyah; Musahwi Musahwi (Universitas Trunojoyo Madura, 2018)
The existence of music as a representation of traditional culture increasingly doubted by various parties. Especially when he has to deal with international music that has a modern genre. In Indonesia, in line with today's global culture, traditional music is slowly being forgotten. Even considered the music peripheral by his own generation because it is not in line with the latest music trends. Is a community of Barak Karinding that plays traditional musical instruments Karinding typical Sundanese, they try to fight the flow. It is important to be studied with regard to the understanding of Karinding musical art, as well as the social values of humanity (local wisdom) that they stretcher in daily life amid the onslaught of global music products today. The type of this research is qualitative, by trying to describe the phenomenon naturally based on the social setting as it is. The results of this study describes among others: a) Karinding music has value, Belief, Patience, Conscious. As a universal message of their music. b) loving art is loving humanity. That is, musical works are not created for the interests of the market as the mindstream of music today, but to develop constructive human beings.